Enfermedades gingivales asociadas a tratamientos de ortodoncia fija, en los y las estudiantes de la Universidad Nacional de Loja de la modalidad de estudio presencial perteneciente al periodo mayo-julio de 2014. - Villalta Valladares, Carlos Eduardo (2014)
Gingival diseases are a diverse family of different and complex pathologies, which are confined to the gum and are the result of various etiologies, without affecting the supporting tissues (ligament, cement, bone). Orthodontics improve dental and skeletal problems, helps oral hygiene, improving alignment and reducing dental occlusal trauma; therefore leads to periodontal health. Oral hygiene can be difficult to maintain during orthodontic treatment; which can cause plaque buildup and inflammation, leading to gum disease. The research work is about gum disease associated with fixed orthodontic treatments. It is descriptive, quantitative and transversal, to determine the frequency of gingival diseases, in “Universidad Nacional de Loja” students. The results showed that the frequency of gum disease is 56% of a sample corresponding to 91 students with orthodontics; considering the sex, higher frequency in males with 57% was found, and according to age it was determined that 18 to 21 have condition corresponding to 78%. With respect to the frequency of brushing, patients with gum disease do it three times a day by 67%, 27% twice, once 4% and more than 3 times 2%. Concluding with this research work, that gum disease is directly related to orthodontics; also that the male is the most affected, according to the age between 18-21 years is more involved, and that the frequency of brushing is not a inversely proportional factor to the frequency of gum disease itself. Keywords: gum disease, orthodontics, gingivitis.